2022
DOI: 10.1002/bse.3298
|View full text |Cite
|
Sign up to set email alerts
|

Climate change performance and financial distress

Abstract: Given the crucial role that environmental accounting plays in sustainable development, this study investigates the relationship between climate change disclosure performance (CCDP) and financial distress as well as the moderating impact of litigation, the existence of a risk committee, the employment of Big4 auditing firms and the level of audit fees. Utilising a sample of the top 300 Australian Securities Exchange (ASX)‐listed non‐financial firms over the period 2008–2019 and ordinary least squares (OLS) regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 131 publications
(217 reference statements)
0
6
0
Order By: Relevance
“…Financial leverage is measured by dividing total liabilities by equity and is denoted as “ FL ”. Long-term borrowing level is measured by dividing long-term debt by total assets and is denoted as “ LTBL ” (Huynh et al ., 2020; Alshahrani et al ., 2022).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Financial leverage is measured by dividing total liabilities by equity and is denoted as “ FL ”. Long-term borrowing level is measured by dividing long-term debt by total assets and is denoted as “ LTBL ” (Huynh et al ., 2020; Alshahrani et al ., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies have shown a link between asset profitability (ROA) and environmental disclosure (Ben-Amar et al. , 2017; Alshahrani et al ., 2022). Akbaş and Canikli (2018) find that the return on assets ratio of firms listed in the BIST100 index had a significantly positive effect on their voluntary participation in CDP reporting in Turkey between 2014 and 2016.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations